Spin Pass Exercise Model on Rugby Game - David David (BIRCU, 2019)
This study aims to develop a spin pass exercise model in rugby game to obtain empirical data about the effectiveness of the spin pass training model on rugby game at DKI Jakarta Rugby Club. The method which is used in this study is Research and Development method of Borg and Gall which consists of ten steps. The subject of the research is DKI Jakarta rugby club athlete. The final result of this study is a model guidebook and a spin pass training video model on rugby games at DKI Jakarta Rugby Club with a total of 18 final models that have gone through expert evaluation, trial and revision, and effectiveness has been tested. The effectiveness of the spin-pass training model in rugby game at DKI Jakarta Rugby Club uses the